Contribution Of The Value Of The Teachings Of Thoriqoh Naqsyabandiyah Kholidiyah To Islamic Education For The Elderly In Wonosobo Penarik Mukomuko - Desiono, Maula (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2024)
This research was motivated by the fact that there were still many people, especially the elderly, who did not enter Thoriqoh Naqsyabandiyah Kholidiyah. These were due to a lack of understanding about Thoriqoh, inadequate feeling, lack of socialization by Thoriqoh administrators, and unstable economic and social factors in the community. The last factor coused that they did not have time or opportunity in joining thoriqoh activities. This type of research was field research using qualitative descriptive research methods. The results of this research show that the values ??of thoriqoh naqsyabandiyah kholidiyah can be applied in Islamic education for the elderly, namely : Consistency in Dhikr and Worship, Cleansing the Heart (Tazkiyatun Nafs), Discipline in Keeping Time (Waro' and Zuhud), Obedience to Teachers and Mentors Spirituality, Simplicity and Tawakal, Awareness of the Afterlife, Mutual Help and Solidarity (Ukhuwah Islamiyah), Patience and Perseverance, Self-Control (Mujahadah), Peace of Heart and Spiritual Balance. Meanwhile, the contributions of Thoriqoh Naqsyabandiyah Kholidiyah values in ??improving the quality of Islamic education for the elderly in Wonosobo village are increasing spiritual calm and happiness, increasing discipline and productivity, strengthening social relations and Islamic brotherhood, deepening awareness of the afterlife, overcoming the challenges of old age patiently. and Tawakal, Forming the Elderly as Spiritual Role Models, Maintaining Mental and Spiritual Balance. The challenges faced in implementing the values ??of thoriqoh naqsyabandiyah kholidiyah among the elderly in Wonosobo Village, Penarik District, Mukomuko Regency are Physical and Health Limitations, Limited Access to Education and Spiritual Guidance, Lack of Understanding of the Teachings of Sufism, Lack of Support from the Social Environment, Differences in Religious Background and Preferences, Psychological and Emotional Barriers, Limited Facilities and Infrastructure, Influence of Local Culture, Difficulty in Internalizing Values.